Hierarchical self-supported ZnAlEu LDH nanotubes hosting luminescent CdTe quantum dots. Issue 53 (17th May 2017) - Morais, Alysson F.; Silva, Ivan G. N.; Sree, Sreeprasanth P.; de Melo, Fernando M.; Brabants, Gert; Brito, Hermi F.; Martens, Johan A.; Toma, Henrique E.; Kirschhock, Christine E. A.; Breynaert, Eric; Mustafa, Danilo
Abstract : Self-assembled, cylindrical LDH nanotubes (∅ 20nm) host large species such as nanodots or bulky substrates in their central cavity, leaving the interlayer space available for anionic sensitizer molecules. Abstract : Self-supported oligo-layered ZnAlEu LDH nanotubes (∅ 20 nm) self-assemble upon controlled hydrolysis of the metal ions (Zn 2+, Al 3+, Eu 3+ ) in the presence of 1, 3, 5-benzenetricarboxylate anions and non-ionic worm-like micelles. Their high surface area and easily accessible cylindrical mesopores (175 m 2 g −1 ; 0.75 cm 3 g −1 ) facilitate interaction with 5 nm CdTe quantum dots, enhancing the overall luminescence behavior.